Persepsi Santriwati Pondok Pesantren Al Jihad Surabaya Terhadap Arah Kiblat - Sholikah, Nurus; Muna, Putri Nailul; Arifin, Rochmalia Faizah; Solikin, Agus; Sholihuddin, Muh. (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2024)
One of the valid requirements for prayer is facing the Qibla, which is often confusing for the Muslim community in Indonesia, both in implementation and understanding. In the view of the four schools of Islamic jurisprudence scholars, there are two opinions about the direction of the Qibla, namely (1) for those who can see the Kaaba directly and (2) vice versa, giving rise to the terms 'ainul Kaaba and jihatul Kaaba. Likewise, with the latest fatwa issued by the MUI regarding the direction of the Qibla, which shows that the Qibla of Indonesian Muslims is facing the Northwest, not just the West. The female students of the Al Jihad Islamic Boarding School in Surabaya, as respondents in the study, of course also have different perceptions from one another. The results of this study are that there are differences in views about the direction of the Qibla among the female students of the Al-Jihad Islamic Boarding School, which can be caused by differences in a person's background in pursuing knowledge previously, namely those who have never attended boarding school or have attended boarding school.